The factors that affecting consumer intention to utilize the electronic payment system in Malaysia - Azman, Hartini; Tan, Zi Yi; Bakri, Mohammed Hariri (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
The Fourth Industrial Revolution digitizes Malaysia's payment system. Nothing is easy when it comes to the payment method except the electronic payment system. Most Malaysian consumers are not ready to embrace the electronic payment system. This paper aims to recognize factors affecting the consumer's intention to utilize the electronic payment system. Literature demonstrates that factors such as attitude, subjective norms, perceived ease of use, perceived usefulnessand perceived security have an effect on the intention of customers to utilizethe electronic payment system. The quantitative analysis was used by 394 respondents from all over Malaysia. Research findings show that attitude, subjective norms, perceived usefulness and perceived security have a significant relationship with customer's intention to utilizethe electronic payment system but the perceived ease of use does not have a significant relationship with consumer intention to utilize the electronic payment system.The result also shows that perceived usefulness has the strongest influence on consumer intention to utilize the electronic payment system in Malaysia.